2011
DOI: 10.1007/s13391-011-0906-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of Y and Fe co-doped SrTio3 perovskites for methane oxidation

Abstract: Y and Fe co-doped SrTiO3 powder with a phase-pure perovskite structure were synthesized by solid state reaction (SSR) and the Pechini method. The catalytic activity of Y0.08Sr0.92FexTi1-xO3-δ (x = 0.1, 0.2, 0.3, and 0.4) for the methane oxidation reaction was evaluated in terms of the iron content in the perovskite lattice. When the CH4/O2 ratio was 0.25, the total oxidation of methane was predominant. Methane oxidation started at 450ºC and increased with increasing temperature. The methane conversion rate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Comentado [JMGV2]: Opino lo mismo, yo acabaría la frase en account partial substitution of titanium by a transition metal cation promoted the formation of oxygen vacancies and reduced valence states of titanium on the SrTiO3 perovskite, modifying the methane oxidation activity [35]. Recently, Wu et al reported the photocatalytic degradation of tetracycline under visible light using SrTiO3 doped with Mn in concentration around 3-7 at.…”
Section: Introductionmentioning
confidence: 99%
“…Comentado [JMGV2]: Opino lo mismo, yo acabaría la frase en account partial substitution of titanium by a transition metal cation promoted the formation of oxygen vacancies and reduced valence states of titanium on the SrTiO3 perovskite, modifying the methane oxidation activity [35]. Recently, Wu et al reported the photocatalytic degradation of tetracycline under visible light using SrTiO3 doped with Mn in concentration around 3-7 at.…”
Section: Introductionmentioning
confidence: 99%
“…The surfaces prepared by the previous method were found poorly active for CO oxidation in the RT‐300 °C range, with no measurable activity at 150 °C. In order to assess the possible influence of surface oxygen vacancies on the reactivity, the samples were annealed at ca . 700 °C for ~30 min under UHV (so‐called ‘reductive pretreatment’) prior to the catalytic tests.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, methane conversion increases with temperature with a sigmoidal profile. Indeed, depending the fixed temperature, different reaction pathway may controls the overall methane catalytic combustion [9,[28][29][30][31]. At low temperature, the combustion is controlled by the surface oxygen vacancies that are activate sites for oxygen adsorption.…”
Section: -6mentioning
confidence: 99%